DAMPAK PERKEMBANGAN VILLA TERHADAP KEHIDUPAN SOSIAL DAN EKONOMI MASYARAKAT KELURAHAN SEMINYAK KECAMATAN KUTA, KABUPATEN BADUNG - I Nyoman Gede Pariyasa; I Wayan Sonder; Fatrisia Yulianie (Forum Manajemen STIMI Handayani Denpasar, 2021)
Seminyak is one of tourist destination area in Bali . The development of tourism in the Seminyak accompanied by a fairly rapid growth of villas has reach the residential areas.The existence of this phenomenon is believed impacting the social and economic life of the community. Therefore, the purpose of this study is to determine the types of impact, the factors that led to the emergence of impact and efforts to do related to the impact of un-concentrated development of villas in Seminyak area. The results showed that un-concentrated villa’s developments in the Seminyak gives social and economic impact of local communities. The social impact such as improving the quality of public education, increasing solidarity between citizens, and rising crime. Impact on the economy field such as increasing employment opportunities, incomes, and also increasing the food prices. Side factor causing the emergence of social impact in terms of the influence of foreign tourists visiting, the quantity and quality of adequate educational facilities, increasing people's income, the immigrant community, location villas scattered, weak oversight of the villa, boost the economy, and the increasing influence of the surrounding environment land prices. Side factor causing the emergence of the economic impact such as growing amount of tourism infrastructure, manpower requirements at all levels, spending and the number of tourist arrivals, the high price of handicraft products, targeted changes to the traders and travelers interest in local food. Efforts to do in the field of social such as, increase security and preserve the stability of the local culture, while in the economic field is classified according to the type of target market stalls.